Diagnóstico de la situación actual de la explotación acuícola, en el cantón Nangaritza, provincia de Zamora Chinchipe - Guamán Aldaz, Humberto Wilmer (2014)
This research is based on an assessment of the current situation of aquaculture production in the canton of Nangaritza Zamora Chinchipe, it was born as an initiative to provide primary information for the project entitled: "STUDY OF THE CURRENT SITUATION AQUACULTURE PRODUCTION OF THE PROVINCE OF ZAMORA CHINCHIPE "; the objective of the project is to identify the productive characteristics of aquaculture farms, determined with the same location of production facilities, study the technological level, socio-economic and productive performance of farms along the cantons. In researching a participatory diagnosis was made using surveys as a means for obtaining information, Socioeconomic issues, such as economic status, education level, number of members dedicated to the activity; General Aspects and Technological level, such as geographical location of each station, freehand sketches stations, systems and methods of production, mirrors and water volumes; Productive parameters as demand for fingerlings by each producer, number of pounds produced per farm, number of pounds offered to the market. In the canton Nangaritza there are 48 producers, with mirrors above 50m2 water, besides existing 52 farmers with less than 50m2 surface water intended for rearing fish for family support, between the two groups covering a total water mirror of 42831.70 m2, and the total water volume of 32328.98 m3. Most of them have 3 years producing and just 1 over 10 years. Mostly only two members are dedicated to the activity, their level of education is primary and your monthly income exceeds three hundred us dollars. Most do not have biosafety systems or customer support, there are no controls, no control in production processes, and no records are kept and very few being maintained. The number of tanks is limited, as many of them employ earth structure, very few concrete or mixed; where red tilapia, black tilapia and some other Amazon fish, the type of production is handmade and in monoculture, the most used are balanced GISIS and ABBA and spending by the same does not exceed three hundred dollars a month is grown, and their production ranges mostly do not exceed four hundred pounds a year. The product sale is direct, the bulk and almost entirely in the local market, the supply of the product by producers not cover the demand, greater production missing. Lack of institutional support, technical assistance brief or nonexistent by the institutions responsible for carrying it out, poor training, is the main problem that has limited the development of the activity.